모바일 헬스 서비스 사용자 특성 분석 및 이탈 예측 모델 개발 - 한정현; 이주연 (시스템엔지니어링학술지, 2021)
As the average life expectancy is rising, the population is aging and the number of chronic diseases is increasing. This has increased the importance of healthy life and health management, and interest in mobile health services is on the rise thanks to the development of ICT(Information and communication technologies) and the smartphone use expansion. In order to meet these interests, many mobile services related to daily health are being launched in the market. Therefore, in this study, the characteristics of users who actually use mobile health services were analyzed and a predictive model applied with machine learning modeling was developed. As a result of the study, we developed a prediction model to which the decision tree and ensemble methods were applied. And it was found that the mobile health service users' continued use can be induced by providing features that require frequent visit, suggesting achievable activity missions, and guiding the sensor connection for user’s activity measurement.
Keywords: Healthcare; Health Management; Mobile Health; Machine Learning; Supervised Learning